Prepare to Defend Yourself . . . How to Age Gracefully and Escape with Your Dignity - Minson, Matthew, 1961- (Book collections on Project MUSE., 2016)
The author of Prepare to Defend Yourself ... How to Navigate the Healthcare System and Escape with Your Life is back. This time Matthew Minson, MD, turns a penetrating and whimsical eye on the medical and social aspects of aging in Prepare to Defend Yourself ... How to Age Gracefully and Escape with Your Dignity. While seeming to simultaneously channel a combination of Benjamin Franklin and Charles Schulz, Dr. Minson goes after bodily changes, behaviors-good and bad, and what everyone can do to make life more bearable and-dare we say it-fun after fifty. Laced with his unique style of poignancy and hu.